KORELASI ANTARA BERAT LAHIR DAN POLA ASUH PADA BALITA USIA 24 – 60 BULAN DENGAN KEJADIAN STUNTING DI BANJARNEGARA - Dian Nirmala; Umi Nur Fajri (Jurnal Ilmiah Medsains, 2022)
The incidence of stunting (short) toddlers is a major nutritional problem faced by Indonesia.Based on the Nutritional Status Monitoring (PSG) data for the last three years, stunting has thehighest prevalence compared to other nutritional problems such as undernutrition, thinness, andobesity. Factors that influence the history of LBW and upbringing. The purpose of the study was todetermine the relationship between LBW and parenting with the incidence of stunting. The researchmethod is quantitative with a case control approach. The sample in this study were toddlers aged 2-5years. The results of the chi square test showed that there was a relationship between birth weight andthe incidence of stunting under five (p value 0.000), there was no relationship between parenting andthe incidence of stunting under five (p value 0.106). Suggestions for health workers in carrying outmidwifery care, especially for patients with a history of LBW, to do care as early as possible so thatthe baby's growth is normal and suppresses the incidence of stunting.